The Comparison of Smile Aesthetic of Males and Females Based on Buccal Corridor and Smile Arc: Perbandingan Estetika Senyum Antara Laki-Laki dan Perempuan Berdasarkan Buccal Corridor dan Smile Arc - Hadi, Lina; Br Sembiring, Puspa Maya; Muttaqin, Zulfan (Dentika: Dental Journal, 2020)
In performing the orthodontic treatments, patients aim to improve their smile esthetical features which are influenced by the position, size, shape, and color of teeth. However, in recent decades, several aesthetical features that have been studied are buccal corridor, smile arc, incisor display, and gingival display. In this study, 32 subjects composed of 16 males and 16 females were photographed from the front-site by using a DSLR camera within smiling states. Smile arc and buccal corridor measurements were performed via Corel Draw 12 program. The extra broad and broad characteristics were found in male subjects which were 31.2% and 18.8% respectively, while the female subjects had a higher broad proportion of 43.7% and extra broad for 6.3%. The smile arc features in male subjects were found were straight smile (34.4%) and consonant smile (15.6%), in contrast, the percentage of the female students had a higher consonant smile (31.3%) than straight smile (18.8%). This study confirmed similar findings regarding the domination of the buccal corridor broad in the female population, whereas the extra broad is dominated by males. By contrast, the smile arc consonant is dominated by females, while the straight feature is dominated by males.